Is the Inability to Marry a Marital Status? Levin v. Yeshiva University and the Intersection of Sexual Orientation and Marital Status in Housing Discrimination - Kravis, Andrew (Columbia Journal of Gender and Law, 2012)
This Article posits that when an unmarried same-sex couple is denied a housing opportunity, the discriminator’s motivation is not always clear. The discriminator may simply deny discriminating altogether, or alternatively may justify his or her actions in one of two ways: either he or she discriminated because the couple was unmarried or because they were presumably not heterosexual. Where state law provides protections for only one of these classes (either unmarried persons or non-heterosexuals) or for neither, unmarried same-sex couples are subject to the whims of discriminatory pretext. Because the Fair Housing Act does not protect against either sexual orientation housing discrimination or marital status housing discrimination, state law governs these cases. Thus, housing providers in the thirty-five states that protect only one or neither of these statuses avoid legal consequences for their discrimination by recharacterizing the facts to fit the permissible form of discrimination. When and if federal marriage equality is enacted, having dual protections for sexual orientation and marital status will reduce or negate the disparate impact created by many courts’ narrow-view analysis of marital status discrimination. The logic is fairly simple: as more LGBT couples get married, the percentage of total unmarried couples that are LGBT should decrease. But as long as sexual orientation discrimination and marital status discrimination are thought of as separate and distinct vectors of discrimination, such as they are in the current drafting of the Housing Opportunities Made Equal (HOME) Act, courts will continue to miss the various contexts in which the two operate simultaneously to freeze the status quo—a society which treats unmarried homosexual couples worse than their married and heterosexual counterparts. To achieve real progress, federal legislators first must pass federal marriage equality, and second must define marital status discrimination to comport with the “broad view” taken by many state courts. Otherwise, housing providers will be free to deny unmarried couples housing, and that practice will continue to have a disparate negative impact on LGBT couples in jurisdictions where they are not allowed to marry.